Flowers through concrete : explorations in Soviet hippieland - Fürst, Juliane, 1973- 1973- (Oxford University Press, 2021)
In the face of disapproval and repression Soviet hippies created a version of Western counterculture, skilfully adapting to, manipulating, and shaping their late socialist environment. This book explores their lives and thoughts